Neurocognitive mechanisms of anxiety: an integrative account - Bishop, Sonia J. (Trends in cognitive sciences, 2007)
Anxiety can be hugely disruptive to everyday life. Anxious individuals show increased attentional capture by potential signs of danger, and interpret expressions, comments and events in a negative manner. These cognitive biases have been widely explored in human anxiety research. By contrast, animal models have focused upon the mechanisms underlying acquisition and extinction of conditioned fear, guiding exposure-based therapies for anxiety disorders. Recent neuroimaging studies of conditioned fear, attention to threat and interpretation of emotionally ambiguous stimuli indicate common amygdala–prefrontal circuitry underlying these processes, and suggest that the balance of activity within this circuitry is altered in anxiety, creating a bias towards threat-related responses. This provides a focus for future translational research, and targeted pharmacological and cognitive interventions.